Genetic abnormalities/syndromes significantly impact perioperative outcomes of conotruncal heart defects - Subhrajit Lahiri; Wernovsky Gil; Salyakina Daria; Gruber Joshua; Jayakar Parul; Burke Redmond; Welch Elizabeth (Annals of Pediatric Cardiology, 2020)
Objectives : The main objective of the study is to characterize the effects of genetic abnormalities/syndromes (GA/S) on perioperative outcomes of cardiac surgeries involving repair of conotruncal heart defects (CTHD). Design : The study involves a single-center retrospective analysis of patients who underwent complete repair of CTHDs (tetralogy of Fallot [TOF], truncus arteriosus, interrupted aortic arch, and ventricular septal defect with coarctation) between January 2000 and December 2015. The primary outcome was the post operative length of stay (PLOS). The secondary outcomes were mortality, cardiac complications, hematologic complications, infections, and number of medications-at-discharge. Setting : Cardiac intensive care unit in a tertiary pediatric hospital in South Florida that performs around 300 open-heart surgeries a year. Subjects : A total of 177 patients with CTHDs who underwent cardiac surgeries in the stated time period were included in the final study cohort. Measurements and Main Results :Majority of patients had TOF (72.5%) and 46 (26%) had GA/S. The most common GA/S was 22q11 deletion (37%). PLOS was significantly increased in patients with GA/S (P < 0.05). Patients with GA/S were 4.5 times more likely to have a postoperative cardiac complication, 4.2 times more likely to have a postoperative infection, and received 1.6 times more medications at discharge than those without GA/S. However, GA/S was not associated with increased perioperative mortality. Black patients were three times more likely to have a longer PLOS than White patients. Conclusions : Perioperative outcomes in patients with GA/S suggested an increased residual cardiovascular disease and increased resource usage. Notably, this is the first study demonstrating the effect of race and ethnicity on PLOS in CTHD patients.